Effective staff management in the academic library - Małgorzata Bańkowska (Rozprawy Społeczne)
Introduction: The aim of the article is to discuss the basic determinants of effective human resource management in the sector of academic libraries. The relationships between the university’s organizational culture and the adopted management styles, as well as the impact of staff policy on employees’ attitudes were analysed. Material and methods: The research was carried out using the method of free (uncategorized) participant observation, conducted by the author during her nine years of work as a director of academic library. The obtained data were supplemented and verified on the basis of conversations with the directors of universities, in particular State Higher Vocational Schools (Polish: państwowe wyższe szkoły zawodowe) and Polish and foreign literature on the subject. Conclusions: The organizational culture of a university, including the adopted system of values and norms as well as the leadership skills of senior and middle management affect the attitudes and commitment of library employees, both in a positive and negative way. The style of management also shapes the image of a library and directly affects the type and level of the services it provides.